IMF Survey, Volume 37, Issue 02. (IMF Survey; IMF Survey ;, 2008)
Financial market turbulence; world growth; global outlook; financial market outlook; subprime fallout; writedowns; risk management; credit rating agencies; prudential oversight; liquidity management; risk measurement; public debt; subprime crisis; central bank liquidity; financial turmoil; open market operations; liquidity; securities valuation; risk modeling; Ghana; bond issue; Niger; debt relief; Millennium Development Goals; fiscal management; fiscal transparency; Latin America; Davos.